Transistor Application of Phenacene Molecules and Their Characteristics (Eur. J. Inorg. Chem. 24/2014). Issue 24 (August 2014) - Kubozono, Yoshihiro; He, Xuexia; Hamao, Shino; Teranishi, Kazuya; Goto, Hidenori; Eguchi, Ritsuko; Kambe, Takashi; Gohda, Shin; Nishihara, Yasushi
Abstract : The inside cover picture shows a representation of the phenacene field‐effect transistor (FET). A thin film or a single crystal of the phenacene molecule is an active layer of the FET. SiO2 can be utilized as a gate dielectric, which becomes a gate capacitor in the FET. The gate voltage can be applied through the heavily doped Si substrate. In this case, the FET device can be recognized as a "top‐contact/bottom‐gate" structure. Furthermore, an ionic liquid such as bmim[PF6 ] forms the electric double layer (EDL) with a thickness of 1 nm, which becomes an effective capacitor in the FET, i. e. low‐voltage operation is observed in the EDL FET. The gate voltage is applied through the gate electrode immersed in the ionic liquid. This device can be recognized as a "top‐contact/top‐gate" structure. A single crystal of the phenacene molecule is shown in the background. Details are presented in the Microreview by Y. Kubozono et al. onp. 3806 ff .